Support low carbon vegetable garden with M+ living lab at Qingshan Village - Zhen, Yan; Wang, Ting; Chen, Kevin Z. (CGIAR System Organization, 2025)
In the context of global climate change and food system transformation, developing low-carbon (zero-carbon) agricultural production models has become a key link to achieving the Sustainable Development Goals. As an important part of a healthy diet, vegetable production has lower resource consumption and greenhouse gas emissions than animal-derived food, but its carbon life-cycle environmental footprint cannot be ignored. As an innovative concept and practical path to transform vegetable production from "traditional carbon source" to "potential carbon sink", "carbon sink vegetable" is currently attracting attention from academia and industry. Based on this, this paper combines academic research and the Chinese case to explain carbon vegetables' scientific connotation, key influencing factors, core implementation techniques and value conversion mechanisms. This study provides a reference for Qingshan Village M + Living Lab Eco-Garden Project by summing up their practical experience.